Beyond the Balassa-Samuelson Effect: Do Remittances Trigger the Dutch Disease?. Issue 1 (2nd January 2023) - Fisera, Boris; Workie Tiruneh, Menbere
ABSTRACT: We investigate the impact of remittance inflows on the real exchange rate using a sample of 134 developing and emerging economies. Using heterogeneous panel cointegration approach, we find that remittances contribute to long-term real appreciation of the domestic currency, which is beyond the level implied by the Balassa-Samuelson effect. Consequently, we find evidence that remittances might contribute to triggering the phenomenon of the Dutch disease. We also find evidence for heterogeneity in the effects of remittances on the real exchange rate: having floating exchange rate, higher economic freedom and higher financial development reduces the long-run appreciation due to remittance inflows.